Identifying Age Based Maturation in the ERP Response to Faces in Children With Autism: Implications for Developing Biomarkers for Use in Clinical Trials - Webb, Sara Jane; Emerman, Iris; Sugar, Catherine; Senturk, Damla; Naples, Adam J.; Faja, Susan; Benton, Jessica; Borland, Heather; Carlos, Carter; Levin, April R.; McAllister, Takumi; Santhosh, Megha; et al. (Frontiers in Psychiatry, 2022)
Recent proposals have suggested the potential for neural biomarkers to improve clinical trial processes in neurodevelopmental conditions; however, few efforts have identified whether chronological age-based adjustments will be necessary (as used in standardized assessments). Event-related potentials (ERPs) demonstrate early differences in the processing of faces versus objects in the visual processing system by 4 years of age and age-based improvement (decreases in latency) through adolescence. Additionally, face processing has been proposed to be related to social skills as well as autistic social-communication traits. While previous reports suggest delayed latency in individuals with autism spectrum disorder (ASD), extensive individual and age based heterogeneity exists. In this report, we utilize a sample of 252 children with ASD and 118 children with typical development (TD), to assess the N170 and P100 ERP component latencies (N170L and P100L, respectively) to upright faces, the face specificity effect (difference between face and object processing), and the inversion effect (difference between face upright and inverted processing) in relation to age. First, linear mixed models (LMMs) were fitted with fixed effect of age at testing and random effect of participant, using all available data points to characterize general age-based development in the TD and ASD groups. Second, LMM models using only the TD group were used to calculate age-based residuals in both groups. The purpose of residualization was to assess how much variation in ASD participants could be accounted for by chronological age-related changes. Our data demonstrate that the N170L and P100L responses to upright faces appeared to follow a roughly linear relationship with age. In the ASD group, the distribution of the age-adjusted residual values was more right-skewed, reflecting that ASD participants were more likely to demonstrate slower latencies than would be expected for a TD child of the same age. Lastly, using age-adjusted values for stratification, we found significant relations between the age-adjusted N170L and face memory and verbal and non-verbal IQ. These data suggest that age must be considered in assessing the N170L and P100L response to upright faces and that additional relations with phenotype became apparent when using adjusted values.